2023
DOI: 10.3390/foods12020362
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Full-Fat and Defatted Hermetia illucens Larvae and Poultry By-Products as Sustainable Protein Sources Improved Fillet Quality Traits in Farmed Barramundi, Lates calcarifer

Abstract: The physicochemical quality and shelf-life of fillets from barramundi, which were fed for 56 days on a mixture of poultry by-product meal (PBM), full-fat Hermetia illucens (FHI), and defatted HI (DHI), were investigated and compared to a fishmeal (FM) control diet. The proximate and total amino acids compositions of the fillets were unaffected by the test diets, while the mixture of PBM and HI larvae improved the sensory quality. An eight-day shelf-life study showed that PBM-HI-based diets improved the texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…In a promising outcome, BSFL meal was shown to improve final fillet quality in rainbow trout (Oncorhynchus mykiss; Borgogno et al 2017) and barramundi (L. calcarifer; Chaklader et al 2022Chaklader et al , 2023b. In these three studies, an improvement in flavour and texture, especially juiciness, was reported.…”
Section: Seafood Qualitymentioning
confidence: 92%
See 2 more Smart Citations
“…In a promising outcome, BSFL meal was shown to improve final fillet quality in rainbow trout (Oncorhynchus mykiss; Borgogno et al 2017) and barramundi (L. calcarifer; Chaklader et al 2022Chaklader et al , 2023b. In these three studies, an improvement in flavour and texture, especially juiciness, was reported.…”
Section: Seafood Qualitymentioning
confidence: 92%
“…Compositional analyses of food allow for precise nutritional labelling and can lead to putative health claims. It is therefore noteworthy that the composition of seafood species grown with alternate ingredients is often provided, and has been shown to be affected by diet (Olsen et al 2004;Mai et al 2006;Moren et al 2006;Olsen et al 2006;El-Rahman and Badrawy 2007;Abdul Kader et al 2011;Kader and Koshio 2012;Friesen et al 2013;Gause and Trushenski 2013;Waagbø et al 2013;Sprague et al 2015;Emery et al 2016;Wong et al 2016;Kim et al 2019;Monge-Ortiz et al 2020;Chaklader et al 2022Chaklader et al , 2023b. This alteration of composition, particularly evident in fatty acid content, has consequences for human nutrition (Blondeau et al 2015;Mensink 2016;Michielsen et al 2019).…”
Section: Food Science and Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the use of H. illucens replacing up to 60% of FM significantly increased flesh hardness and decreased cohesiveness in Japanese eel ( Anguilla japonica ) 75 . A recent study tested a mixture of H. illucens larvae meal and poultry by‐products as FM alternatives in the diets of juvenile barramundi ( Lates calcarifer ) 76 . H. illucens inclusion improved muscular microstructure and texture profile based upon the hardness, chewiness, cohesiveness, and gumminess, with 27.8% defatted H. illucens generated the same effects as 35% full‐fat H. illucens .…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturementioning
confidence: 99%
“…For example, the partial replacement of fish meals with BSF can improve the sensory and physicochemical qualities of farmed barramundi filets (Chaklader et al, 2022).…”
Section: Introductionmentioning
confidence: 99%